(untitled) (Revista horizonte, 2014)
Based on the sport pedagogy, this research addressed the problems of women’s football training an intervention based on the reduced forms plays in space. OBJECTIVE: Demonstrate that in game situations based activities can generate appropriate to the problems in the game motor responses improving stock performance with ball unconditioned responses effectiveness criteria stereotyped. METHODS: An individual approach was used with follow- on design of participant observation in training situation a verification procedure of motor behaviors ball a 23 college women, to which pretest, posttest innovation and at the end of the intervention was applied. RESULTS: The mean differences between the pretest and posttest with no test for independent samples were significant at a level (p = < 0.05), both the number of contacts with ball (p = 0,000), hits for ball (p = 0,000), and to save the errors (p = 0.017). CONCLUSION: Shapes played in confined space produce significant improvements in the actions with the ball female soccer players in our sample and only the mistakes with the ball, in the variable pass the adversary" (AP), no significant changes (p = 0.730) were observed.